La structure d’Everyman - Colette Stévanovitch (Anglophonia)
In the English Morality play Everyman, translated from the Dutch Elckerlijk, the protagonist is repeatedly affected by desertion (after having been abandoned by his friends and kinfolks, his own qualities eventually fail him). This repetitive motif has often been considered a flaw in the design. Contrary to that opinion, the author holds that repetition is a key element in the structure of a play constructed as a series of embedded frames.